The emerging digital economy : entrepreneurship, clusters, and policy - Johansson, B.; Karlsson, Charlie, 1945-; Stough, Roger (Springer, 2006)
Chapters include: Entrepreneurship, clusters and policy in the emerging digital economy, Industrial cluster analysis and technology policy decisions in functional regions, and Cities in the Internet age.- Resumé vydavatel
Papers presented at the Uddevalla Symposium held June 2002 at Uddevalla, Sweden.
Keywords: informační a komunikační technologie; ekonomie; regionální ekonomie; technologický rozvoj; technika a společnost; information and communication technology; economics; regional economics; technological development; technology and society; elektronické knihy; sborníky konferencí; electronic books; proceedings of conferences